Choroidal thickness in patients with coronary artery disease. - Meleha Ahmad; Patrick A Kaszubski; Lucy Cobbs; Harmony Reynolds; Roland Theodore Smith (PLoS ONE)
Purpose To evaluate choroidal thickness (CTh) in patients with coronary artery disease (CAD) compared to healthy controls. Design Cross-sectional. Methods Setting: Ambulatory clinic of a large city hospital. Patient population: Thirty-four patients had documented CAD, defined as history of >50% obstruction in at least one coronary artery on cardiac catheterization, positive stress test, ST elevation myocardial infarction, or revascularization procedure. Twenty-eight age-matched controls had no self-reported history of CAD or diabetes. Patients with high myopia, dense cataracts, and retinal disease were excluded. Observation procedures: Enhanced depth imaging optical coherence tomography and questionnaire regarding medical and ocular history. Main outcome measures: Subfoveal CTh and CTh 2000 μm superior, inferior, nasal, and temporal to the fovea in the left eye, measured by 2 readers. Results CTh was significantly lower in patients with CAD compared to controls at the subfoveal location (252 vs. 303 μm, P = 0.002) and at all 4 cardinal macular locations. The mean difference in CTh between the 2 groups ranged from 46 to 75 μm and was greatest in the inferior location. Within the CAD group, CTh was significantly lower temporally (P = 0.007) and nasally (P<0.001) than subfoveally, consistent with the pattern observed in controls. On multivariate analysis, CAD was negatively associated with subfoveal CTh (P = 0.006) after controlling for diabetes, hypertension, and hypercholesterolemia. Conclusions and relevance Patients with CAD have a thinner macular choroid than controls, with preservation of the normal spatial CTh pattern. Decreased CTh might predispose patients with CAD to high-risk phenotypes of age-related macular degeneration such as reticular pseudodrusen and could serve as a potential biomarker of disease in CAD.